2012
DOI: 10.1164/rccm.201104-0729oc
|View full text |Cite
|
Sign up to set email alerts
|

Refusal of Intensive Care Unit Admission Due to a Full Unit

Abstract: Delayed ICU admission due to a full unit at first referral is associated with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 37 publications
4
94
2
1
Order By: Relevance
“…17 We postulate that there are likely systemrelated and patient-related factors that influence this relationship and contribute to what has come to be known as Bfailure to rescue.^1 8,19 System-related factors may include general inpatient floor staffing models and provider-patient ratios, 20 temporal issues including the time of day and day of the week at which deterioration occurs, 21 adherence to vital sign monitoring protocols, 22 and ICU bed availability. 7,23,24 There are also cultural barriers preventing staff from calling for assistance, [25][26][27][28] and nurse/physician providers often do not accurately self-assess the quality of their care for clinically deteriorating patients. 28 Patient factors, such as severity of illness, age, 29 medical comorbidities, and the number and type of specific criteria heralding deterioration 12,13,30 may all play a role as well.…”
Section: Discussionmentioning
confidence: 99%
“…17 We postulate that there are likely systemrelated and patient-related factors that influence this relationship and contribute to what has come to be known as Bfailure to rescue.^1 8,19 System-related factors may include general inpatient floor staffing models and provider-patient ratios, 20 temporal issues including the time of day and day of the week at which deterioration occurs, 21 adherence to vital sign monitoring protocols, 22 and ICU bed availability. 7,23,24 There are also cultural barriers preventing staff from calling for assistance, [25][26][27][28] and nurse/physician providers often do not accurately self-assess the quality of their care for clinically deteriorating patients. 28 Patient factors, such as severity of illness, age, 29 medical comorbidities, and the number and type of specific criteria heralding deterioration 12,13,30 may all play a role as well.…”
Section: Discussionmentioning
confidence: 99%
“…This is where all beds in an ICU are occupied with critically ill patients, and the unit is asked to admit a suitable new patient. This means that a current patient has to be discharged before they are ready (Robert et al 2012), or out of daytime hours when ward areas are not optimally set up to accept a precarious discharge. Discharging a patient 48 h before they are ready increases the chance of postdischarge mortality by up to 39%, with discharges at night and investing (Glac 2009;Smith 2014), the importance (e.g.…”
Section: Risk Trade-offs In the Icumentioning
confidence: 99%
“…For instance, in 2008, a pregnant Japanese woman died after being refused by eight hospitals because none of them had a vacant bed (Coco Masters, 2009). Furthermore, research conducted by Robert, Reignier, and Tournoux (2012) showed that patients whose admissions to the Intensive Care Unit (ICU) were delayed due to the lack of vacancy were subject to a much higher risk of mortality.…”
Section: Introductionmentioning
confidence: 99%